Organic particle, diaphragm, preparation method of diaphragm, battery and electric device

CN119522509APending Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051158.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-02-25

Smart Images

  • Figure CN119522509A_ABST
    Figure CN119522509A_ABST
Patent Text Reader

Abstract

The invention discloses an organic particle, a diaphragm, a preparation method of the organic particle, a battery and an electric device. The organic particle provided by the invention has a sunken structure, and the sunken structure is formed by inwards sinking a part of the surface of the organic particle. The diaphragm comprises a base film and a coating layer arranged on at least one surface of the base film, and the coating layer contains the organic particles. The organic particles have good liquid storage capacity. The diaphragm is endowed with good air permeability, electrolyte storage capacity and hot melting characteristic, more importantly, the electrolyte backflow capacity of the diaphragm can be remarkably improved, and the charging and discharging efficiency of the battery can be remarkably improved. The battery comprises the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Organic particles, diaphragm and preparation method thereof, battery and electrical device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to organic particles and a preparation method thereof, a diaphragm and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.

[0003] As battery applications expand, especially in recent years with the rapid development of electric vehicles, power batteries have experienced rapid development and a sharp increase in demand. However, battery safety performance has also received increasing attention and has become one of the key factors restricting the expansion of battery applications.

[0004] Among battery safety issues, the most prominent is the runaway exothermic reaction within the battery. While safety-modified separators have been developed to some extent, they can improve their safety against thermal runaway reactions, but in actual production and application, they have also created new problems. For example, when the battery is discharged at high rates, the electrolyte reflux capacity deteriorates, further reducing the separator's storage capacity, thereby affecting the electrochemical performance of the ion battery, including charge-discharge efficiency and cycle performance.

[0005] Summary of the Invention

[0006] In view of the above problems, the embodiments of the present application provide organic particles, a diaphragm and a preparation method thereof, a battery and an electrical device to solve the technical problem that the existing safety modified diaphragm has unsatisfactory electrolyte reflux capacity.

[0007] First, embodiments of the present application provide organic particles. These organic particles have a concave structure, formed by inward depression of a portion of the surface of the organic particles. Due to their excellent liquid storage capacity and thermal melting properties, these organic particles can impart excellent air permeability, electrolyte storage capacity, and electrolyte reflux capabilities to the separator, significantly improving battery charge and discharge efficiency.

[0008] In some embodiments, the depth of the recessed structure is ≥0.2 μm, and can be optionally 0.2 μm to 2.45 μm, or optionally 0.4 μm to 0.65 μm.

[0009] In some embodiments, the diameter of the recessed structure is 0.4 μm to 4.9 μm, and optionally 0.8 μm to 1.3 μm.

[0010] The concave structure of this depth and diameter range can further enhance the liquid storage capacity of the organic particles, improve the electrolyte wettability and electrolyte reflux ability of the separator, and significantly improve the battery charge and discharge efficiency. In addition, the thermal melt response rate is sensitive.

[0011] In some embodiments, the organic particles are hollow particles, and the concave structure is formed by the inward depression of a partial shell of the hollow particle. Such hollow particles have stronger liquid storage capacity and mechanical properties such as rebound, as well as a high hot melt response rate.

[0012] In some embodiments, the shell thickness of the hollow particles is 0.05 μm to 3 μm, and optionally 0.15 μm to 0.2 μm. Hollow particles within this shell thickness range have relatively higher mechanical properties such as rebound and liquid storage capacity, thereby improving the liquid storage capacity of the separator and the electrolyte reflux capacity.

[0013] In some embodiments, the volume distribution particle size Dv50 of the organic particles is 0.5 μm to 5 μm, and can be optionally 1 μm to 1.5 μm.

[0014] In some embodiments, the organic particles have a glass transition temperature of 90°C to 120°C, and optionally 100°C to 115°C.

[0015] The volume distribution particle size Dv50 and glass transition temperature range of the organic particles can further improve the electrolyte wettability and electrolyte reflux capacity of the separator and improve the safety performance of the battery.

[0016] In some embodiments, the organic material of the organic particles contains a polymer, and the polymer satisfies at least one of the following conditions:

[0017] The weight average molecular weight of the polymer is 100,000 to 3,000,000, and can be optionally 1,000,000 to 1,500,000;

[0018] The polymer includes at least one of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, and acrylonitrile.

[0019] By selecting organic materials for organic particles, the electrolyte reflux capacity of the diaphragm can be further improved, the battery charging and discharging efficiency can be significantly improved, and the hot melt response rate is more sensitive.

[0020] In a second aspect, an embodiment of the present application provides a method for preparing organic particles. The method for preparing organic particles in an embodiment of the present application comprises the following steps:

[0021] preparing an organic particle raw material; the interior of the organic particle raw material is filled with a volatile solvent;

[0022] The volatile solvent is removed, and a portion of the surface of the organic particle raw material is made to be concave inward to form a concave structure, thereby obtaining organic particles.

[0023] The organic particles prepared by the preparation method of the embodiment of the present application have a concave structure, and thus have the good liquid storage capacity and mechanical properties such as morphology rebound of the organic particles in the embodiment of the text application above, giving the diaphragm good air permeability and electrolyte storage capacity and electrolyte reflux capacity.

[0024] In some embodiments, the organic particle raw material is a polymer particle raw material, and the method for preparing the polymer particle raw material comprises the following steps:

[0025] Performing a first emulsion polymerization reaction on a first polymer monomer containing a carboxyl group to obtain a first polymer particle emulsion containing a carboxyl group;

[0026] mixing a second polymer monomer with the first polymer particle emulsion to form a second polymer monomer coating layer on the outer surface of the first polymer particle, and performing a second emulsion polymerization reaction to obtain a second polymer particle emulsion;

[0027] The volatile base is mixed with the second polymer particle emulsion, and the volatile base is allowed to undergo expansion and neutralization reaction with the carboxyl groups contained in the carboxyl group-containing polymer to obtain an organic particle raw material.

[0028] The organic particle raw material is prepared by the above-mentioned expansion method, which can effectively fill the interior of the organic particle raw material with a volatile solvent, and can allow the organic particle raw material to seep out during heat treatment so that part of the surface of the organic particle raw material is concave inward to form a concave structure, thereby improving the morphological stability of the formed organic particles.

[0029] In an embodiment, the mass ratio of the second polymer monomer to the first polymer particles contained in the first polymer particle emulsion is (10 to 40): (0.3 to 0.5).

[0030] In an embodiment, the carboxyl group-containing polymer monomer includes at least one of acrylic acid, methacrylic acid, maleic acid, and fumaric acid.

[0031] In an embodiment, the second polymer monomer includes at least one of styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, and acrylonitrile.

[0032] In some embodiments, the method for removing the volatile solvent includes heat-treating the organic particle raw material until the volatile solvent is completely evaporated; wherein the heat treatment temperature is below the melting point of the organic particle raw material.

[0033] In some embodiments, the heat treatment temperature is 40°C to 50°C, and optionally 45°C to 48°C.

[0034] In some embodiments, the heating rate of the heat treatment is 6°C / min to 16°C / min, and can be optionally 9°C / min to 12°C / min.

[0035] Heat treatment and its heat treatment conditions can control the volatile solvent from seeping out from the interior of the organic particle raw material, so that the surface portion of the organic particle raw material is concave inward to form a concave structure, and the concave structure can be controlled, thereby improving the liquid storage capacity and mechanical properties of the organic particles such as morphology rebound.

[0036] In some embodiments, the volatile solvent includes water, which can be effectively removed during the heat treatment process and ensures that the morphology of the prepared organic particles is stable.

[0037] In a third aspect, an embodiment of the present application provides a diaphragm. The diaphragm of the embodiment of the present application includes a base film and a coating applied on the surface of the base film, wherein the coating contains organic particles of the embodiment of the present application or organic particles prepared by the method for preparing organic particles of the embodiment of the present application. The diaphragm of the embodiment of the present application has excellent electrolyte wettability and electrolyte reflux capacity, which can significantly improve the electrochemical properties of the battery, including charge and discharge efficiency and cycle performance. It also gives the diaphragm the property of melting at abnormal temperatures, thereby improving the safety performance of the battery.

[0038] In some embodiments, the dry weight content of the organic particles in the coating is ≥ 22 wt%, and can be 22 wt% to 32 wt%, based on the total dry weight of the coating as 100%. By controlling and adjusting the content of the organic particles in the coating, the liquid storage capacity and electrolyte reflux capacity of the separator can be further improved.

[0039] In some embodiments, the coating further comprises an inorganic particle filler. By adding the inorganic particle filler to the coating, the mechanical properties of the coating, such as compressive strength, are improved, while the separator's wettability, electrolyte reflow capacity, and electrolyte storage capacity are enhanced, thereby improving the battery's charge and discharge efficiency.

[0040] In some embodiments, the inorganic particulate filler satisfies at least one of the following conditions:

[0041] The dry weight content of the inorganic particulate filler in the coating is 16 wt % to 26 wt % based on the total dry weight of the coating as 100%;

[0042] The volume distribution particle size D of the inorganic particle filler v 50 is 0.5μm to 5μm, optionally 1μm to 1.5μm;

[0043] The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0044] The inorganic particle filler has any of the above characteristics and can further improve the air permeability, heat shrinkage resistance, liquid storage capacity and other properties of the diaphragm.

[0045] In some embodiments, the coating further comprises a cured binder. By adding the binder to the coating, the bonding force between the organic particles or the inorganic particle fillers can be effectively enhanced, thereby improving the mechanical properties of the coating and enhancing the bonding force between the coating and the base film.

[0046] In some embodiments, based on the total dry weight of the coating being 100%, the dry weight content of the binder in the coating after curing is 15 wt % to 25 wt %.

[0047] In some embodiments, the thermal decomposition temperature of the binder is ≥160°C, and can be selected from 160°C to 300°C.

[0048] By controlling the content of the binder in the coating, the mechanical properties of the coating and the bonding force between the coating and the base film can be further enhanced, and the air permeability, electrolyte reflux capacity and liquid storage capacity of the diaphragm can be further enhanced.

[0049] In some embodiments, the base film has a thickness of 4 μm to 7 μm; and / or

[0050] In some embodiments, the coating has a thickness of 2 μm to 5 μm; and / or

[0051] The surface density of the coating is 1 g / m 2 Up to 10g / m 2 , optional 2g / m 2 Up to 4g / m 2 .

[0052] By controlling the characteristics of the base film, coating thickness and surface density, the permeability, wettability to electrolyte and reflux ability of the diaphragm can be further improved, while the diaphragm's liquid storage capacity can be improved, thereby improving the battery's charge and discharge efficiency and safety performance.

[0053] In a fourth aspect, an embodiment of the present application provides a method for preparing a diaphragm. The method for preparing a diaphragm in an embodiment of the present application comprises the following steps:

[0054] providing a base film and a coating slurry containing organic particles;

[0055] Applying the coating slurry on at least one surface of the base film and drying it to form a coating to obtain a diaphragm;

[0056] The organic particles are the organic particles of the present application or the organic particles prepared by the organic particle preparation method of the embodiments of the present application.

[0057] The diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has excellent air permeability, good wettability and reflux ability to the electrolyte, can improve the charging and discharging efficiency of the battery, and can also effectively reduce the risk of thermal runaway of the battery and improve the safety performance of the battery.

[0058] In some embodiments, the coating slurry further comprises an inorganic particle filler and a binder; wherein the mass ratio of the organic polymer particles, the inorganic particle filler and the binder in the coating slurry is (22 to 32): (16 to 26): (15 to 25).

[0059] In some embodiments, the coating slurry has a solid content of 30 wt % to 40 wt %.

[0060] In some embodiments, the coating slurry has a viscosity of 100 mPa·s to 1000 mPa·s at 25°C.

[0061] The coating slurry having the above characteristics can improve the film-forming quality, the quality of the coating and the performance such as the air permeability.

[0062] In some embodiments, the binder is added in the form of a binder aqueous solution, and the binder aqueous solution has at least one of the following conditions:

[0063] The viscosity of the binder aqueous solution at 25° C. is 3000 mPa·s to 10000 mPa·s;

[0064] The solid content of the binder aqueous solution is 40 wt % to 50 wt %.

[0065] By controlling and adjusting the viscosity of the binder aqueous solution or the solid content at the same time, the slurry stability and dispersibility are further improved, thereby improving the quality of the coating and further improving the properties of the membrane such as the air permeability mentioned above.

[0066] In some embodiments, the coating slurry is applied at a rate of 10 m / min to 100 m / min, optionally 1 m / min to 50 m / min; and / or

[0067] The drying temperature is 40°C to 50°C, optionally 45°C to 48°C; and / or

[0068] The drying time is 3 minutes to 6 minutes, and optionally 4 minutes to 5 minutes.

[0069] By adjusting the coating process conditions, the film quality, thickness and permeability can be adjusted and optimized.

[0070] In a fifth aspect, embodiments of the present application provide a battery. The battery of the present application embodiment includes a positive electrode, a negative electrode, and a separator laminated between the positive and negative electrodes, wherein the separator is the separator described in the embodiments of the present application or a separator prepared using the separator preparation method of the embodiments of the present application. The battery of the present application embodiment has excellent charge and discharge efficiency and high safety.

[0071] In some embodiments, the coating is disposed on one surface of the separator, with the coating facing the negative electrode. By only incorporating the coating on one surface of the separator, the overall thickness of the separator can be effectively reduced, thereby increasing the energy density of the battery.

[0072] In a sixth aspect, an embodiment of the present application provides an electrical device, wherein the electrical device includes a battery according to an embodiment of the present application, and the battery is used to provide electrical energy. The safety of the electrical device according to the embodiment of the present application is significantly improved.

[0073] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0075] FIG1 is a schematic flow chart of a method for preparing organic particles according to an embodiment of the present application;

[0076] FIG2 is a schematic flow chart of a method for preparing a diaphragm according to an embodiment of the present application;

[0077] FIG3 is a schematic structural diagram of an embodiment of a secondary battery of the present application;

[0078] FIG4 is an exploded schematic diagram of the secondary battery shown in FIG3 ;

[0079] FIG5 is a schematic structural diagram of an embodiment of a battery module according to the present application;

[0080] FIG6 is a schematic structural diagram of an embodiment of a battery pack according to the present application;

[0081] FIG7 is a schematic diagram of the exploded structure of the battery pack shown in FIG6 ;

[0082] FIG8 is a schematic diagram of an embodiment of an electric device including a secondary battery according to an embodiment of the present application as a power source;

[0083] FIG9 is a scanning electron microscope (SEM) image of the diaphragm in Example A1 of the present application; wherein FIGa is an SEM at room temperature (25° C.), and FIGb is an SEM after heating at 115° C. for 15 minutes;

[0084] FIG10 is a scanning electron microscope (SEM) image of the separator in Comparative Example A1 of the present application at room temperature (25° C.).

[0085] The accompanying drawings in the specific implementation manner are as follows:

[0086] 10. Secondary battery cell, 11. Housing, 12. Electrode assembly, 13. Cover plate;

[0087] 20. Battery module;

[0088] 30. Battery pack, 31. Box, 32. Lower box. DETAILED DESCRIPTION

[0089] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0090] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0091] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0092] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0093] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0094] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0095] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0096] In the description of the embodiments of the present application, unless otherwise expressly specified or limited, technical terms such as "installed," "connected," "connected," and "fixed" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integration; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; internal connections between two components or interactions between two components. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application based on specific circumstances.

[0097] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.

[0098] In ion batteries such as lithium-ion batteries, the diaphragm is one of the important components, which is set between the positive and negative pole pieces to separate the positive and negative poles of the battery, preventing the two poles from contacting and short-circuiting, and preventing the Li-ion battery from passing through the positive and negative poles. + Therefore, in addition to having good electrolyte wettability, liquid retention, and mechanical strength, the separator also needs to have properties such as thermal stability that have a significant impact on battery safety, as battery safety performance is increasingly valued.

[0099] Currently, the method of improving the thermal stability and other properties of the diaphragm is to modify the diaphragm, such as doping or coating modifiers such as flame retardant additives, fiber-like substances, electrochemically inert ceramics, etc. during the preparation process of the diaphragm, so as to achieve the purpose of improving the thermal stability and other properties of the diaphragm and thus improving battery safety.

[0100] While current methods like doping or coating can improve separator performance, such as thermal stability, to a certain extent, the inventors discovered during their research that when exothermic reactions within the battery accumulate to a certain level, the modified separator is unable to promptly block the continued reaction, making it difficult to promptly reduce or prevent internal short circuits or even thermal runaway. Therefore, this approach is not ideal for improving battery safety, such as thermal runaway.

[0101] To improve the diaphragm's ability to suppress thermal runaway, current methods include modifying the diaphragm surface, such as adding a modified coating. However, the inventors discovered that adding a modified coating to the diaphragm can negatively impact the diaphragm's air permeability. Furthermore, when the battery is subjected to stress during assembly and normal operation, the modified coating further reduces the diaphragm's air permeability or the diaphragm's ability to reflux the electrolyte, thereby reducing the battery's electrochemical properties, such as cycling performance and charge / discharge efficiency, affecting the battery's normal operation and performance.

[0102] In addition, research has found that during the charge and discharge process, the electrodes, such as the negative electrode, generally expand, squeezing out the electrolyte in the electrode assembly. High-rate discharge requires rapid electrolyte return to the bare cell. However, existing coatings have defects such as high-temperature resistance, electrolyte swelling, and external force extrusion, which slow the electrolyte's return to the electrode assembly. When the battery is discharged at a high rate, the electrolyte cannot flow back to the electrode assembly in time, which significantly affects the battery's high-rate discharge.

[0103] Therefore, in order to improve the separator's response rate to thermal runaway and its ability to reflux the electrolyte, the inventors have proposed a new organic granular material. This organic granular material forms a coating that imparts to the separator, effectively improving the separator's response rate to thermal melt and enhancing battery safety. It also imparts good electrolyte wettability and electrolyte reflux capacity, and can also improve the separator's liquid storage capacity, thereby enhancing the battery's charge and discharge efficiency, cycle performance, and safety.

[0104] organic particles

[0105] In a first aspect, embodiments of the present application provide an organic particle. The organic particle of the present application has a recessed structure. In one embodiment, a scanning electron microscope image of the organic particle shows its morphology as shown in FIG9A . The organic particle 1 has a recessed structure 11, which is formed by a portion of the surface of the organic particle being recessed inward.

[0106] Because the organic particles in the embodiments of the present application have a recessed structure, they possess excellent liquid storage capacity. When formed as a coating on the surface of the base membrane of the separator, they impart excellent air permeability and electrolyte storage capacity to the separator. More importantly, they significantly enhance the electrolyte reflux capacity of the separator, significantly improving the battery's charge and discharge efficiency. Furthermore, the organic particles with this recessed structure exhibit hot-melt properties, enhancing the battery's safety.

[0107] After testing, the size of the recessed structures contained in the organic particles of the embodiment of the present application is at least within any of the following ranges:

[0108] The depth of the recessed structure can be ≥0.2μm, optionally 0.2μm to 2.45μm, optionally 0.4 to 0.65μm; therefore, in the exemplary embodiment, the depth of the recessed structure can be typical but non-limiting depths such as 0.2μm, 0.5μm, 1μm, 1.2μm, 1.5μm, 1.7μm, 2μm, 2.2μm, 2.45μm, etc.

[0109] The diameter of the recessed structure may be 0.4 μm to 4.9 μm, and further may be 0.8 μm to 1.3 μm. In an exemplary embodiment, the diameter of the recessed structure may be 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3 μm, 3.3 μm, 3.5 μm, 3.8 μm, 4 μm, 4.3 μm, 4.5 μm, 4.9 μm, and other typical but non-limiting diameters.

[0110] The concave structure with this depth and diameter range can further enhance the liquid storage capacity of the organic particles, while also improving mechanical properties such as the organic particle morphology and rebound. This gives the separator containing the organic particles a coating with improved air permeability and electrolyte reflux capacity, significantly improving battery charge and discharge efficiency. Furthermore, the structure is sensitive to abnormal thermal melting, further enhancing battery safety.

[0111] The depth of the recessed structure refers to the vertical distance from the bottom of the recessed structure 11 in Figure 1 to the surface of the organic particle 1. The diameter of the recessed structure refers to the diameter of the cavity formed by the recessed structure 11 in Figure 1, such as the diameter at the opening of the recessed structure 11. The depth of the recessed structure is half the diameter of the recessed structure, as measured by surface scanning electron microscopy (SEM). For irregular recessed structures, the average value of at least three measurements can be used.

[0112] In addition, the organic particles may contain at least one recessed structure, that is, one or more than two recessed structures.

[0113] In one embodiment, the organic particles are hollow particles, and the concave structure is formed by the inward depression of a partial shell of the hollow particle. A hollow particle refers to a particle having a shell, and a hollow cavity structure formed by the shell. The concave structure is formed by the shell portion being concave into the hollow cavity structure. The hollow particles have stronger liquid storage capacity and mechanical properties such as rebound, as well as a high hot melt response rate, thereby further improving the electrolyte wettability and electrolyte reflux capacity of the diaphragm containing the hollow particles to form a coating, which can significantly improve the battery charge and discharge efficiency and battery safety performance.

[0114] When the organic particles are the above-mentioned hollow particles, in the embodiment, the shell thickness of the hollow particles can be 0.05μm to 3μm, and further can be 0.15μm to 0.2μm. In the exemplary embodiment, the shell thickness can be 0.05μm, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm and other typical but non-limiting diameters. Then at this time, the inner diameter of the hollow particles is the outer diameter of the hollow particles minus the thickness of the shell. The hollow particles in this shell thickness range have relatively higher mechanical properties such as rebound, thereby improving the liquid storage capacity of the coating, thereby improving the liquid storage capacity of the membrane containing the hollow particle coating, that is, the embodiment of the present application, and improving the electrolyte reflux capacity of the membrane.

[0115] In the embodiment, the volume distribution particle size Dv50 of the organic particles in the above embodiments can be 0.5μm to 5μm, and further can be 1μm to 1.5μm. In the exemplary embodiment, the particle size Dv50 can be, but is not limited to, typical non-limiting particle sizes such as 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, and 1.5μm. The particle size Dv50 of the organic particles refers to the outer diameter (diameter) of the organic particles. Organic particles in this particle size range have higher mechanical capabilities such as rebound, further improving the electrolyte wettability and electrolyte reflux capacity of the diaphragm containing the organic particles to form a coating, which can significantly improve the battery charge and discharge efficiency and battery safety performance.

[0116] In the embodiments described above, the organic particles have a glass transition temperature of 90°C to 120°C, and further can be 100°C to 115°C. This glass transition temperature range gives the organic particles a high thermal melt response rate. When the internal temperature of the battery abnormally rises to the glass transition temperature, the organic particles can promptly melt and seal the pores of the base film of the separator, mitigating or preventing the risk of thermal runaway and improving the safety performance of the battery.

[0117] For example, in some embodiments, the organic material of the organic particles in the above embodiments may include a polymer, and the organic particles may be polymer particles. In some embodiments, the polymer may have a weight-average molecular weight of 100,000 to 3,000,000, or further may have a weight-average molecular weight of 1,000,000 to 1,500,000. The molecular weight can be determined using gel permeation chromatography (GPC) with reference to GBT 27843-2011, "Test Method for Low Molecular Weight Component Content in Chemical Polymers."

[0118] In exemplary embodiments, the polymer may include at least one of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, and acrylonitrile. By selecting the organic material of the organic particles, such as these polymers, the mechanical properties of the organic particles in the aforementioned embodiments, such as morphology and rebound, can be effectively improved. This improves the electrolyte reflux capacity of the coating containing the organic particles, i.e., the separator in the embodiments of the present application, significantly improving the battery's charge and discharge efficiency. Furthermore, the hot melt response rate is more sensitive, further enhancing the battery's safety.

[0119] In some embodiments, the morphology of the organic particles in the above embodiments may include at least one of spherical, quasi-spherical, and rod-shaped. Organic particles with these morphologies have high compressive and rebound mechanical properties, and also have improved liquid storage capacity, thereby further enhancing the electrolyte reflux and liquid storage capacity of the separator.

[0120] Preparation method of organic particles

[0121] In a second aspect, the present invention provides a method for preparing the organic particles described above. The process flow of the method for preparing the organic particles described in the present invention is shown in FIG1 , and includes the following steps:

[0122] S01: preparing an organic particle raw material, wherein the interior of the organic particle raw material is filled with a volatile solvent;

[0123] S02: removing the volatile solvent contained in the organic particle raw material, and making the surface of part of the organic particle raw material concave inward to form a concave structure, thereby obtaining organic particles.

[0124] In the preparation method of the diaphragm of the embodiment of the present application, since the organic particle raw material is a volatile solvent, when the volatile solvent is removed in step S02, due to the pressure difference or further based on the deformation of the organic particle raw material, part of the shell of the organic particle raw material is sunken to form a concave structure.

[0125] The method for preparing organic particles in the embodiment of the present application removes the volatile solvent contained in the organic particle raw material, thereby causing the surface of the organic particle raw material to partially indent, forming the organic particles in the embodiment of the text application. Therefore, the organic particles prepared by the preparation method of the embodiment of the present application have a concave structure, and thus have the good liquid storage capacity and mechanical properties such as morphology rebound of the organic particles in the embodiment of the text application. After forming a coating on the surface of the base film of the diaphragm, it gives the diaphragm good air permeability and electrolyte storage capacity, and at the same time has good electrolyte reflux capacity. It also has a sensitive hot melt response rate. In addition, the process conditions of the method for preparing organic particles in the embodiment of the present application are reliable, which can ensure the stability of the morphology and physicochemical properties of the prepared organic particles.

[0126] Step S01:

[0127] The volatile solvent contained in the organic particle raw material should be filled inside the organic particle raw material, so that the volatile solvent can seep out or further evaporate to cause internal negative pressure and deformation of the organic particle raw material, causing part of the surface to sink inward to form a concave structure.

[0128] In the embodiment, the volatile solvent filled in the organic particle raw material can be water, of course, it can also be other volatile solvents, such as but not limited to volatile alcohols, etc. As long as it can generate negative pressure and deformation to form a concave structure inside the organic particle raw material after volatilization, the corresponding volatile solvent is within the scope disclosed in the embodiment of the present application. The specific amount can be determined according to the type of organic particle raw material or its preparation method. When these volatile solvents can be effectively removed by seepage during the heat treatment process, the morphology of the prepared organic particles can be ensured to be stable.

[0129] In the embodiment, the organic particle raw material in step S01 can be prepared by a method capable of achieving internal coating of volatile solvent particles, such as an emulsion method, to form an in-situ coating layer on the surface of the volatile solvent liquid. Alternatively, the following expansion method can be used.

[0130] As in the embodiment, when the organic particle raw material is a polymer particle raw material, the method for preparing the polymer particle raw material includes the following steps:

[0131] S11: performing a first emulsion polymerization reaction on a first polymer monomer containing a carboxyl group to obtain a first polymer particle emulsion containing a carboxyl group;

[0132] S12: mixing the second polymer monomer with the first polymer particle emulsion to form a second polymer monomer coating layer on the outer surface of the first polymer particle, and performing a second emulsion polymerization reaction to obtain a second polymer particle emulsion;

[0133] S13: mixing the volatile base with the second polymer particle emulsion, and allowing the volatile base to undergo a neutralization reaction with the carboxyl groups contained in the carboxyl group-containing polymer to obtain an organic particle raw material.

[0134] The organic particle raw material is prepared by the above-mentioned expansion method, which can effectively fill the interior of the organic particle raw material with a volatile solvent, which can seep out during the heat treatment in step S02 to make part of the surface of the organic particle raw material concave inward to form a concave structure, thereby improving the morphological stability of the formed organic particles.

[0135] After the first emulsion polymerization reaction in step S11, the first polymer monomer containing carboxyl groups forms a polymer particle emulsion containing carboxyl groups. The polymer particles containing carboxyl groups constitute the core layer of the organic particles.

[0136] Since an emulsion polymerization reaction is carried out in step S11, the reaction system in step S11 may further contain components such as a first emulsifier, water, and a first initiator.

[0137] In the embodiment, in the first emulsion polymerization reaction, the first emulsifier, the first polymer monomer, and the first initiator can be mixed in a mass ratio of emulsifier:first polymer monomer:first initiator of (0.3 to 0.5):(98.7 to 96.5):(1 to 3). By controlling the mixing ratio of the components, the efficiency of the first emulsion polymerization reaction is improved.

[0138] In addition, the emulsion polymerization reaction in step S11 can be carried out under the following conditions: heating and stirring in a nitrogen environment, the temperature is 70° C. to 80° C., and the stirring speed is 800 rpm to 1200 rpm.

[0139] The first polymer monomer can be controlled to be mixed with the first emulsifier, the first initiator, etc. in a dropwise addition manner, for example, the addition rate can be 5 g / min to 10 g / min, and the total reaction time can be 6 h to 8 h.

[0140] In an exemplary embodiment, the first polymer monomer may include at least one of acrylic acid, methacrylic acid, maleic acid, and fumaric acid.

[0141] In an embodiment, the first emulsifier may include at least one of anionic, nonionic or reactive emulsifiers, anionic emulsifiers, and the like. In an exemplary embodiment, the anionic emulsifier may include sodium lauryl sulfate, sodium dodecylbenzenesulfonate, potassium stearate, sodium dioctyl sulfosuccinate, sodium dodecyldiphenyloxydisulfonate, ammonium salt of nonylphenoxyethyl poly(1)ethoxyethyl sulfate, sodium styrene sulfonate, sodium dodecylallyl sulfosuccinate, linseed oil fatty acid, sodium or ammonium salt of ethoxylated nonylphenol phosphate, sodium octoxyno1-3-sulfonate, sodium cocoyl sarcosine, sodium 1-alkoxy-2-hydroxypropyl sulfonate, sodium α-olefin (C14-C16) sulfonate, sulfate of hydroxyalkanol, tetrasodium N-(1,2-dicarboxyethyl)-N-octadecyl sulfosuccinamate, disodium N-octadecyl sulfosuccinamate, disodium alkoxyamidopolyethoxysulfosuccinate, disodium ethoxylated nonylphenol sulfosuccinate half ester, and sodium ethoxyethyl sulfate.

[0142] In an embodiment, the first initiator may include at least one of tert-butyl peroxide, alkali metal persulfate, ammonium persulfate, etc. Among them, the alkali metal persulfate may include sodium persulfate, potassium sulfate, lithium sulfate, etc.

[0143] In the exemplary embodiment, the conditions of the first emulsion polymerization reaction can be adjusted and controlled according to the characteristics of the initiator, monomer, etc., such as adjusting and controlling the temperature and time, so that the first polymer monomer undergoes a sufficient polymerization reaction.

[0144] In step S12, the second polymer monomer forms a coating on the surface of the first polymer particles, forming a precursor of the organic particles. After the second emulsion polymerization reaction, the second polymer monomer polymerizes to form a polymer shell layer that coats the first polymer particles. In this way, in the prepared second polymer particle emulsion, the interior of the second polymer particles contains carboxyl groups.

[0145] Since step S12 also performs an emulsion polymerization reaction, the reaction system of step S12 may further contain a second initiator and other components. The second initiator should be an initiator that can at least polymerize the hydrophobic polymer monomer. For example, the second initiator may be the same as or different from the first initiator. Of course, the second initiator should also be relatively sufficient to allow the second polymer monomer to fully polymerize and form a shell layer.

[0146] In the embodiment, the mass ratio of the second polymer monomer to the first polymer particles contained in the first polymer particle emulsion is (10 to 40): (0.3 to 0.5). By controlling the amount of the second polymer monomer added, the thickness of the second polymer monomer coating layer, i.e., the shell layer, can be effectively adjusted, thereby adjusting the size of the recessed structure formed in step S02, thereby improving the liquid storage capacity and mechanical properties such as compressive strength of the organic particles.

[0147] In an exemplary embodiment, the second polymer monomer includes at least one of styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, and acrylonitrile. These second polymer monomers can form a polymer shell and improve the liquid storage capacity and mechanical properties such as compressive strength of the organic particles.

[0148] Since step S12 also involves an emulsion polymerization reaction, the reaction system in step S12 may further contain components such as a second initiator and a second emulsifier. The second initiator should be an initiator capable of at least causing the second polymer monomer to undergo polymerization. For example, the second initiator may be the same as or different from the first initiator. Of course, the second initiator should also be present in a relatively sufficient amount to allow the second polymer monomer to fully undergo polymerization and form a shell. The second emulsifier may be the same as or different from the first emulsifier.

[0149] In addition, during the mixing process of the second polymer monomer and the first polymer particle emulsion, a bridging agent may be added. In an embodiment, the bridging agent may include at least one of ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, propylene glycol diacrylate, triethylene glycol dimethacrylate, 1,1,1-trimethylolpropane trimethacrylate, pentaerythritol trimethacrylate, and divinylbenzene. In an embodiment, the bridging agent may be added in a mass ratio of (0.5 to 1.5) to (10 to 40) of the bridging agent to the second polymer monomer. The addition of the bridging agent can enhance the integrity of the second polymer monomer coating layer and the efficiency of the coating.

[0150] When the system of the second emulsion polymerization reaction in step S12 contains both a bridging agent and an emulsifier, the second polymer monomer, the bridging agent, the second emulsifier, and the first polymer particle emulsion can be mixed in a ratio of the second polymer monomer: the bridging agent: the second emulsifier: the core layer emulsion = (10 to 40): (0.5 to 1.5): (0.3 to 0.5): (60 to 80). By controlling the mixing ratio of the components, the efficiency of the second emulsion polymerization reaction is improved, and the coating integrity of the polymer coating layer formed by the second polymer monomer is improved.

[0151] The conditions of the second emulsion polymerization reaction can be adjusted and controlled according to the characteristics of the second initiator, the second polymer monomer, etc., such as adjusting and controlling the temperature and time so that the second polymer monomer undergoes a sufficient polymerization reaction to form a polymer coating layer. In an embodiment, the conditions of the second emulsion polymerization reaction can be heating and stirring under a nitrogen environment, the temperature is 80°C to 90°C, and the stirring speed is 500rpm to 800rpm. In addition, the second polymer monomer can be added dropwise, such as in the exemplary embodiment, the dropwise addition rate is 5g / min to 10g / min, and the total reaction time is 6h to 8h.

[0152] In step S13, after the volatile base is mixed with the second polymer particle emulsion, the volatile base will penetrate into the second polymer particles contained in the second polymer particle emulsion, thereby being able to undergo a neutralization reaction with the carboxyl groups in the second polymer particles, so that the volatile base can generate gas or volatilize, thereby causing the volume of the second polymer particles to expand to form polymer particle raw materials.

[0153] The volatile base may include, but is not limited to, aqueous ammonia, etc. In addition, during the expansion and neutralization reaction in step S13, the reactants may be subjected to appropriate heating treatment to enhance the penetration of the volatile base into the second polymer particles and improve the neutralization reaction with the carboxyl groups, thereby enhancing the expansion effect of the second polymer particles.

[0154] Step S02:

[0155] The purpose of removing the volatile solvent contained in the organic particle raw material is to make the volatile solvent seep out from the organic particle raw material, so that the negative pressure generated inside the organic particle raw material causes the surface of the organic particle raw material to be concave inward, thereby forming the concave structure described above.

[0156] In an embodiment, the method for removing the volatile solvent contained in the organic particle raw material may include heat-treating the organic particle raw material until the volatile solvent is completely evaporated. The heat treatment temperature should be below the melting point of the organic particle raw material to ensure the morphology of the organic particle raw material is stable. Specifically, the heat treatment temperature should be avoided to avoid excessively high temperatures that may cause adverse deformation of the morphology of the organic particle raw material, thereby ensuring that the organic particles have good mechanical properties such as good liquid storage capacity and morphological resilience.

[0157] When the above-mentioned heat treatment is used to remove the volatile solvent, in an embodiment, the temperature of the heat treatment can be 40°C to 50°C, optionally 45°C to 48°C. In exemplary embodiments, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, and other typical but non-limiting temperatures. By controlling the temperature of the organic particle raw material, the volatile solvent can be controlled to seep out from the interior of the organic particle raw material, or further volatilize, and the organic particle raw material can be dried. In addition, this temperature range effectively improves the stability of the prepared organic particle morphology, thereby improving its mechanical properties such as liquid storage capacity, compressive strength, and morphological rebound.

[0158] In embodiments, the heat treatment may be performed at a specific heating rate to the aforementioned heat treatment temperature. For example, in embodiments, the heating rate may be 6°C / min to 16°C / min, optionally 9°C / min to 12°C / min. In exemplary embodiments, the heating rate may be 6°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, and other typical but non-limiting temperatures. By controlling the heating rate, the rate of volatile solvent exudation and the negative pressure within the organic particle raw material can be adjusted, thereby adjusting the size of the formed recessed structures, further adjusting the morphology of the organic particles, and adjusting and improving their mechanical properties such as liquid storage capacity, compressive strength, and morphological resilience.

[0159] In addition, the size of the negative pressure generated can be adjusted to adjust the size of the organic particles into solid particles or hollow particles, thereby adjusting and optimizing the mechanical properties of the organic particles, such as liquid storage capacity, compression resistance, and morphology rebound.

[0160] diaphragm

[0161] In a third aspect, embodiments of the present application provide a diaphragm. The diaphragm of the present application embodiment includes a base film and a coating disposed on at least one surface of the base film. The coating contains organic particles, which are the organic particles described in the embodiments of the present application.

[0162] In the diaphragm of the present application embodiment, the base film contained therein constitutes the matrix of the diaphragm of the present application embodiment and performs the normal function of the diaphragm. The coating is disposed on the base film and modifies the base film, i.e., the diaphragm matrix. The organic particles contained in the coating are the organic particles of the above-mentioned embodiment of the present application, that is, the organic particles contained in the coating have a concave structure.

[0163] Therefore, the diaphragm of the embodiment of the present application has excellent air permeability and electrolyte reflux capacity due to the presence of the organic particles with a concave structure in the embodiment of the present application in its coating, which can significantly improve the electrochemical properties of the battery, including charge and discharge efficiency and cycle performance. It also gives the diaphragm the property of melting at abnormal temperatures. When the temperature inside the battery abnormally rises to the glass transition temperature of the organic particles, the organic particles in the coating can melt in time and close the pores contained in the base film, thereby reducing or preventing the chemical reactions in the electrolyte and the positive and negative electrode crosstalk reactions and the migration of metal ions that continue to proceed inside the battery, alleviating or terminating thermal runaway and improving the safety performance of the battery. Among them, the migration of the metal ions includes lithium ions and metal precipitation from active materials, etc., to prevent them from passing through the diaphragm and depositing on the surface of the electrode, especially the negative electrode, or further forming dendrites. The positive-negative electrode crosstalk reaction refers to the release of oxygen when the positive electrode active material of the battery undergoes a phase change at high temperature. The oxygen can diffuse to the negative electrode through the diaphragm and react with the negative electrode, etc., and release a large amount of heat; it also includes the hydrogen released from the negative electrode at high temperature, which diffuses to the positive electrode through the diaphragm and reacts with the positive electrode, etc., and releases a large amount of heat.

[0164] In some embodiments, in each of the above embodiments, the dry weight content of the organic particles in the coating can be ≥ 22 wt %, and further can be 22 wt % to 32 wt %, based on the total dry weight of the coating as 100%. By controlling and adjusting the content of the organic particles in the coating, if controlled within this range, the separator's liquid storage capacity and electrolyte reflux capacity can be further improved, and the separator can also be improved to prevent or reduce the risk of thermal runaway of the battery.

[0165] In some embodiments, the coatings included in the separators of the aforementioned embodiments may also contain inorganic particulate fillers. Adding inorganic particulate fillers to the coatings can, on the one hand, improve the coating's air permeability and mechanical properties, enhancing the permeability and operational stability of the separator during battery production and normal operation; on the other hand, they can synergize with the aforementioned organic particles, further improving the separator's air permeability, thereby enhancing the separator's electrolyte reflux and storage capacity, thereby improving the battery's charge and discharge efficiency. Furthermore, the inorganic particulate fillers ideally form a uniform mixture with the aforementioned organic particles in the coating.

[0166] In an embodiment, the dry weight content of the inorganic particle filler in the coating can be 16 wt % to 26 wt %. By controlling the content ratio of the inorganic particle filler and the organic particles in the coating, the synergistic effect between the inorganic particle filler and the organic particles can be enhanced while fully volatilizing the respective effects of the inorganic particle filler as described above. This further improves the good air permeability and mechanical properties of the separator, while further improving the separator's electrolyte reflux capacity, liquid storage capacity, and response to battery thermal anomalies, thereby improving the battery's charge and discharge efficiency and safety performance.

[0167] In the embodiment, the volume distribution particle size D of the inorganic particle filler is v 50 is 0.5μm to 5μm, and can be optionally 1μm to 1.5μm. By adjusting the inorganic particle filler, it is compounded with the organic particle size, and works together with the organic particles in the above particle size range to improve the permeability of the diaphragm and the electrolyte reflux capacity and liquid storage capacity. As tested, the permeability of the diaphragm can reach the permeability performance shown in Table 2 below. Moreover, when the battery experiences thermal anomalies, such as when the temperature rises to the glass transition temperature of the organic particles, the inorganic particle filler in this particle range can fully exert its skeleton effect, causing the organic particles to melt, improve the efficiency of sealing the base membrane pores, and reduce the risk of thermal runaway of the battery.

[0168] In an embodiment, the inorganic particle filler may include at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0169] In an exemplary embodiment, the inorganic material of the inorganic particles having a dielectric constant of 5 or more includes boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m La m Zr 1-n TinO3、Pb(Mg3Nb 2 / 3 )O3-PbTiO3, and at least one of their respective modified inorganic particles, 0<m<1, 0<n<1.

[0170] In an exemplary embodiment, the inorganic material of the inorganic particles having ion conductivity but not storing ions includes Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7;

[0171] In an exemplary embodiment, the inorganic material of the electrochemically reactive inorganic particles includes at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0172] By selecting the material type of the inorganic particle filler, the above-mentioned effect of the inorganic particle filler is improved, the synergistic effect between the inorganic particle filler and the organic particles is further improved, the mechanical stability, air permeability and liquid storage capacity of the diaphragm of the embodiment of the present application and the reflux capacity of the electrolyte are improved, and the charging and discharging efficiency and safety performance of the battery are further improved.

[0173] Based on the organic particles and inorganic particulate fillers described above, in this exemplary embodiment, the inorganic particulate filler contained in the coating is boehmite particles, and the material of the organic particles includes a polymer, specifically polyethylene, specifically low-density polyethylene. Compounding the boehmite particles with the organic particles containing low-density polyethylene significantly enhances the synergistic effect between the organic particles and the inorganic particulate filler, further improving the separator's electrolyte reflux and storage capacity, and further enhancing the battery's charge and discharge efficiency and safety.

[0174] In some embodiments, the coatings included in the separators of the aforementioned embodiments further contain a cured binder. The addition of a binder to the coating effectively enhances the bonding between the organic particles or, further, the inorganic particulate fillers, thereby improving the mechanical properties of the coating and enhancing the bonding between the coating and the base film. Furthermore, the binder can synergize with the organic particles or, further, with the inorganic particulate fillers, further improving the permeability of the separator and its ability to reflux the electrolyte.

[0175] In an embodiment, the dry weight content of the binder in the coating can be 15 wt % to 25 wt % based on the total dry weight of the coating as 100%. By controlling the content of the binder in the coating, the mechanical properties of the coating and the adhesion between the coating and the base film can be further enhanced, and the permeability of the separator and its electrolyte reflux and storage capacity can be further enhanced, thereby further improving the charge and discharge efficiency and safety performance of the battery.

[0176] In the embodiment, the thermal decomposition temperature of the cured binder is higher than 160°C, and can be selected from 160°C to 300°C. By selecting the decomposition temperature characteristic of the binder, the thermal stability of the coating and base film bond is improved, the function of the separator is fully utilized, the electrochemical performance of the battery is improved, and the risk of thermal runaway of the battery is reduced.

[0177] In an embodiment, the binder can be a water-based binder. The water-based binder can be a water-soluble binder or an emulsion binder. In an exemplary embodiment, the binder can include at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin. These binders can enhance the bonding force between organic particles or further inorganic particle fillers, thereby improving the mechanical properties of the coating and enhancing the bonding force between the coating and the base film. The diaphragm can further adjust the electrolyte reflux capacity and enhance the role of the molten organic particles in sealing the base film pores when the battery is thermally abnormal, thereby improving the battery's charge and discharge efficiency and other electrochemical properties and safety performance.

[0178] In an embodiment, when the coating contains both the above-mentioned inorganic particle filler and the binder, the dry weight ratio of the above-mentioned organic particles, inorganic particle filler, and binder in the coating can be (22 to 32): (16 to 26): (15 to 25). By controlling the content ratio of the three components in the coating, the above-mentioned effects of each component and the synergistic effect between the three components are further enhanced, thereby further improving the permeability of the separator and the reflux capacity of the electrolyte, thereby improving the charge and discharge efficiency and safety performance of the battery.

[0179] Based on the coating schemes described in the above embodiments, in some embodiments, the coating thickness can be 2 to 5 μm. In exemplary embodiments, the coating thickness can be 2 μm, 3 μm, 4 μm, 5 μm, and other typical but non-limiting thicknesses. By controlling the coating thickness, the content of components such as the organic particles can be controlled, thereby adjusting and enhancing the ability of the organic particles to fully exert the aforementioned effects, improving the permeability of the separator, the electrolyte reflux capacity, and the separator's liquid storage capacity, thereby improving the battery's charge and discharge efficiency and safety performance.

[0180] After testing, the surface density of the coating contained in the above-mentioned embodiments can be controlled at 1g / m 2 Up to 10g / m 2 , optional 2g / m 2 Up to 4g / m 2 By controlling and optimizing these properties of the coating, the membrane's mechanical properties such as compressive strength, liquid storage capacity, and electrolyte reflux capacity can be further improved, thereby further improving the battery's electrochemical performance and safety performance.

[0181] In addition, the coating included in the separators of the above embodiments can be provided on one surface of the base film, or on two opposing surfaces of the base film. Based on considerations such as battery energy density, in the embodiments, the coating is provided on one surface of the base film, i.e., the opposing surface of the base film is not provided with the coating.

[0182] The base film contained in the separator of each embodiment above can be an organic separator. For example, in the embodiment, the thickness of the base film can be 4 to 7 μm. In other embodiments, the air permeability of the base film can be 180s / 100cc to 240s / 100cc. In the exemplary embodiment, the material of the base film includes at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalene. The base films with these characteristics and materials can be combined with the above coating and play a synergistic role on the basis of giving full play to the role of the battery separator, so that the separator has a higher electrolyte reflux capacity and improves the charge and discharge efficiency and safety performance of the battery.

[0183] In some embodiments, the above-mentioned base membrane can also be a modified base membrane, such as a base membrane modified with at least one modifier such as flame retardants, fiber-like substances, electrochemically inert ceramics, etc., to improve the thermal stability of the base membrane, to cooperate with the above-mentioned coating, and further improve the mechanical properties and safety performance of the diaphragm of the embodiment of the present application.

[0184] Method for preparing diaphragm

[0185] In a second aspect, the present invention provides a method for preparing a diaphragm. The process flow of the method for preparing a diaphragm according to the present invention is shown in FIG2 . The method for preparing a diaphragm according to the present invention may include the following steps:

[0186] S03: providing a basement membrane;

[0187] S04: providing coating slurry;

[0188] S05: coating the coating slurry on at least one surface of the base film, performing a drying process to form a coating layer, and obtaining a separator.

[0189] In the method for preparing the diaphragm of the present embodiment, a coating slurry is applied to form a coating on the surface of the base film, and the coating is then bonded to the surface of the base film. Since the method for preparing the diaphragm of the present embodiment is intended to prepare the diaphragm of the above embodiment, the formed coating contains organic particles, and the organic particles, like the organic particles of the above embodiment, have a concave structure.

[0190] The diaphragm preparation method of the embodiment of the present application prepares organic particles with a concave structure into a coating slurry, and directly forms a film on the base film, so that the prepared diaphragm is combined with the coating on at least one surface to achieve the modification effect of the coating on the base film.

[0191] Then, the coating is the coating contained in the diaphragm of the embodiment of the above-mentioned application. Therefore, the diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has the excellent air permeability and good electrolyte reflux capacity of the diaphragm of the embodiment of the above-mentioned application, which can improve the charge and discharge efficiency of the battery, and can also effectively reduce the risk of thermal runaway of the battery, thereby improving the safety performance of the battery. In addition, the process parameters of the diaphragm preparation method of the embodiment of the present application are controllable, and the quality and electrochemical performance of the prepared diaphragm are stable.

[0192] Step S03:

[0193] The base film in step S03 may be the base film contained in the separator of the embodiment of the above-mentioned application. Therefore, the base film may be the base film contained in the separator of the embodiment of the above-mentioned application. As in the embodiment, the thickness of the provided base film may be 4 μm to 7 μm, and the air permeability may be 180 s / 100 cc to 240 s / 100 cc. The material thereof may include at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.

[0194] Step S04:

[0195] Since the coating slurry in step S04 is a slurry for forming the coating contained in the diaphragm of the above text application embodiment, the coating slurry must contain organic particles and a solvent. In the embodiment, it may further contain an inorganic particle filler and a binder. Therefore, the organic particles contained in the coating slurry, or the material types and content ratios of the inorganic particle fillers and binders further contained therein are the same as the types and content ratios of the organic particles, inorganic particle fillers and binders contained in the coating of the diaphragm of the above text application embodiment. Therefore, in order to save space, the types, content ratios, etc. of organic particles, inorganic particle fillers and binders will not be described in detail here.

[0196] In order to further improve the film-forming quality of the coating slurry and improve the quality and air permeability of the coating, in one embodiment, the solid content of the coating slurry can be 30wt% to 40wt%; in other embodiments, the viscosity of the coating slurry at 25°C is 100mPa·s to 1000mPa·s.

[0197] In some embodiments, when the coating slurry in step S04 is formed by mixing organic particles with inorganic particle fillers and a binder in a solvent; then the mass ratio of organic particles, inorganic particle fillers, binder and water in the coating slurry can be (22 to 32): (16 to 26): (15 to 25): (18 to 30). This ratio refers to the mixing ratio of the binder to the organic particles and inorganic particle fillers before curing. By adjusting the ratio of the three, the film-forming quality of the coating slurry is improved, and the air permeability and related mechanical properties of the formed coating are enhanced, thereby improving the reflux capacity of the diaphragm to the electrolyte.

[0198] The binder may be a pre-cured binder, such as the pre-cured aqueous binder described above. In an exemplary embodiment, the binder may be a pre-cured binder comprising at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin.

[0199] For example, in the embodiment, the binder is added in the form of a binder aqueous solution to effectively adjust the viscosity of the coating slurry, improve the dispersion uniformity and stability of the coating slurry components, and improve the film-forming quality of the coating slurry. When the binder is added in the form of a binder aqueous solution, in the embodiment, the viscosity of the binder aqueous solution can be 3000mPa·s to 10000mPa·s at 25°C; in other embodiments, the solid content of the binder aqueous solution is 40wt% to 50wt%. By controlling and adjusting the viscosity of the binder aqueous solution or the solid content at the same time, the positive effect of the binder on the coating slurry can be further improved, further improving the slurry stability and dispersibility, thereby improving the quality of the coating, and further improving the performance of the diaphragm such as the above-mentioned permeability and the reflux capacity of the electrolyte.

[0200] In addition, there is no specific order between step S03 and step S04 above. The order can be adjusted according to actual production, or they can be performed simultaneously.

[0201] Step S05:

[0202] The purpose of applying the coating slurry to the base film in step S04 is to form a wet film on the base film, i.e., the coating layer before drying. The coating method is not limited; any method capable of forming a film of the coating slurry on the base film is within the scope of the embodiments disclosed herein, including, but not limited to, brushing, roller coating, and spraying. Furthermore, the coating process conditions can be further adjusted to adjust and optimize the film quality, thickness, and air permeability.

[0203] For example, in the embodiment, the coating slurry in step S04 is coated at a rate of 10 m / min to 100 m / min, and further at 10 m / min to 50 m / min. This coating rate can improve the quality of the coating, adjust the coating thickness and the air permeability of the membrane, etc.

[0204] The drying process is primarily intended to remove the solvent from the wet film. The drying temperature should be below the melting point of the organic particles and should ensure coating quality and stability. For example, in the embodiment, the drying temperature can be 40 to 50°C, optionally 45 to 48°C. In exemplary embodiments, typical but non-limiting temperatures such as 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, and 50°C are possible. Furthermore, the drying temperature can be increased at a rate of 6°C / min to 16°C / min, optionally 9°C / min to 12°C / min, to the drying temperature. Within this drying temperature range, the drying time should be sufficient, such as 3 to 6 minutes, optionally 4 to 5 minutes.

[0205] Battery

[0206] Thirdly, embodiments of the present application provide a battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes. The separator is the separator described in the embodiments of the present application. Therefore, the battery of the embodiments of the present application has excellent charge and discharge efficiency and high safety.

[0207] In the examples, the separator is coated only on one surface, with the coated surface facing the negative electrode. By orienting the coating toward the negative electrode, the separator can fully demonstrate the functions described in the examples above, such as improved electrolyte wettability, reflux, and storage capacity, while also enhancing battery safety. Coating only one surface effectively reduces the overall thickness of the separator, increasing the battery's energy density.

[0208] In some embodiments, the battery of the present application can be a secondary battery. When the battery of the present application is a secondary battery, it includes a positive electrode, a separator, and a negative electrode. Specifically, the negative electrode of the secondary battery is the negative electrode of the embodiment described above, and the negative electrode contains the modified artificial graphite of the embodiment described above.

[0209] In this way, the battery of the embodiment of the present application, specifically the secondary battery, has high energy density, high charge and discharge efficiency, good cycle stability, and high safety.

[0210] In an embodiment, the secondary battery of the present application may include any one of a battery cell, a battery module, and a battery pack.

[0211] A battery cell is a battery cell comprising a battery housing and a cell encapsulated within the housing. The shape of a battery cell is not particularly limited and can be cylindrical, square, or any other shape. A square-shaped battery cell 10 is shown in FIG3 .

[0212] In some embodiments, as shown in Figure 4, the outer packaging of the battery cell 10 may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 is used to cover the opening to close the receiving cavity. The positive electrode, diaphragm and negative electrode contained in the secondary battery of the embodiment of the present application can be formed into an electrode assembly 12 through a winding process and / or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 10 may be one or more, which can be adjusted according to actual needs.

[0213] The preparation method of the battery cell 10 is well known. In some embodiments, the positive electrode, separator, negative electrode, and electrolyte can be assembled to form the battery cell 10. As an example, the positive electrode, separator, and negative electrode can be wound or laminated to form the electrode assembly 12. The electrode assembly 12 is placed in an outer package, dried, and then injected with electrolyte. The battery cell 10 is then vacuum packaged, allowed to stand, formed, and shaped.

[0214] A battery module is assembled from the battery cells 10 , that is, it may contain a plurality of battery cells 10 , and the specific number can be adjusted according to the application and capacity of the battery module.

[0215] In some embodiments, FIG5 is a schematic diagram of an exemplary battery module 20. As shown in FIG5 , in the battery module 20, multiple battery cells 10 may be arranged sequentially along the length of the battery module 20. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 10 may be secured together using fasteners.

[0216] Optionally, the battery module 20 may further include a housing having an accommodation space, and the plurality of battery cells 10 may be accommodated in the accommodation space.

[0217] A battery pack is assembled from the battery cells 10 described above, and may contain multiple battery cells 10, wherein multiple battery cells 10 may be assembled into the battery module 20 described above. The specific number of battery cells 10 or battery modules 20 contained in a battery pack may be adjusted according to the application and capacity of the battery pack.

[0218] In the embodiment, Figures 6 and 7 are schematic diagrams of an exemplary battery pack 30. The battery pack 30 may include a battery box and multiple battery modules 20 disposed within the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 covers the lower box body 32 and forms an enclosed space for accommodating the battery modules 20. The multiple battery modules 20 may be arranged in any manner within the battery box.

[0219] Electrical devices

[0220] Fourthly, embodiments of the present application further provide an electrical device comprising the battery of the aforementioned embodiments, which may further comprise a secondary battery. The battery can serve as both a power source and an energy storage unit for the electrical device. Consequently, the electrical device of the embodiments of the present application has a long standby or battery life.

[0221] Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc. These electrical devices may use secondary batteries, battery modules, or battery packs based on their usage requirements.

[0222] Figure 8 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0223] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.

[0224] Example

[0225] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0226] 1. Examples of organic particles and membranes and their preparation methods

[0227] Example A1

[0228] This embodiment provides an organic particle, a diaphragm containing the organic particle, and a method for preparing the same. The organic particle in this embodiment is a hollow particle, wherein the shell of the hollow particle is partially recessed inward to form a concave structure. The dimensions of the hollow particle and the concave structure are shown in Table 1 below. The hollow particle material includes a polymer of methyl methacrylate and styrene.

[0229] The separator of this embodiment includes a PE base film and a coating layer bonded to one surface of the PE base film. The PE base film has a thickness of 7 μm, and the coating layer has a thickness of 4 μm. The coating layer contains the organic particles of this embodiment.

[0230] The method for preparing the organic particles and the diaphragm of this embodiment includes the following steps:

[0231] S1. Preparation of hollow particle emulsion:

[0232] S11. Preparation of nuclear layer:

[0233] Sodium dodecylbenzenesulfonate (emulsifier): methyl methacrylate: ammonium persulfate (initiator) = 0.3:98.7:1 by mass were added to the reactor, using water as the solvent, and heated with stirring under a nitrogen atmosphere at 75°C for 6 hours; then cooled to room temperature to obtain an acidic core layer emulsion;

[0234] S12. Preparation of shell layer:

[0235] The components were added to a reactor in a mass ratio of styrene: bridging agent (ethylene glycol dimethacrylate): volatile base (ammonia water): emulsifier (sodium dodecylbenzenesulfonate): core layer emulsion = 40:1.5:0.3:58.2, heated and stirred under a nitrogen environment, and kept warm at 80°C for 6 hours; the volatile base penetrated and neutralized the core to obtain a hollow particle emulsion, which was filled with water.

[0236] S2. Preparation of diaphragm coating slurry:

[0237] The organic particles prepared in step S1 are mixed with copolymerized polypropylene wax emulsion, polyacrylonitrile, boehmite, and water in a ratio of 25%:25%:20%:30% of organic particles: polyacrylonitrile: boehmite: water. All materials are added to a double planetary stirring tank, and then stirred at 30 rpm and 2000 rpm for 3 hours, with vacuum defoaming throughout the process; the viscosity of the coating slurry is controlled between 500 mPa·s and 800 mPa·s (25°C);

[0238] S3. Preparation of a membrane with organic particles having a concave structure:

[0239] The coating slurry from step S2 was applied to one side of a 7-μm thick PE base film to form a wet film. The film was then dried to form a 2-μm thick coating on one side of the PE base film. The temperature was raised to 45°C at a rate of 9°C / min during drying, and the temperature was maintained for 5 minutes. This resulted in a separator with organic particles having a recessed structure. The particle size, wall thickness, and recess diameter of the organic particles are detailed in Table 1.

[0240] Example A2

[0241] This embodiment provides an organic particle, a membrane containing the organic particle, and a method for preparing the same. The organic particle of this embodiment is identical to that of embodiment A1 except for the different concave diameter.

[0242] The separator of this embodiment has the same features as the separator of embodiment A1 except that the organic particles are different. The organic particles contained in the separator of this embodiment are the organic particles provided in this embodiment.

[0243] The preparation method of the organic particles and the diaphragm in this embodiment refers to the preparation method of the organic particles and the diaphragm in Example A1, except that the temperature rise rate during drying in step S3 is adjusted to 12°C / min, rising to 48°C, and the heat preservation and drying time is 4 minutes.

[0244] Example A3

[0245] This embodiment provides an organic particle, a separator containing the organic particle, and a method for preparing the same. The organic particles of this embodiment are identical to the hollow particles in Example A1 except for the different size.

[0246] The separator of this embodiment has the same features as the separator of embodiment A1 except that the organic particles are different. The organic particles contained in the separator of this embodiment are the organic particles provided in this embodiment.

[0247] The preparation method of the organic particles and the diaphragm in this embodiment refers to the preparation method of the organic particles and the diaphragm in Example A1, except that in step S11, the sodium dodecylbenzenesulfonate (emulsifier): methyl methacrylate: ammonium persulfate (initiator) = 0.5:96.5:3; in step S12, the styrene: bridging agent (ethylene glycol dimethacrylate): emulsifier (sodium dodecylbenzenesulfonate): core layer emulsion = 19.2:0.5:0.3:80.

[0248] Example A4

[0249] This embodiment provides an organic particle, a separator containing the organic particle, and a method for preparing the same. The organic particle of this embodiment is identical to that of embodiment A1 except that the first polymer monomer is different.

[0250] The separator of this embodiment has the same features as the separator of embodiment A1 except that the organic particles are different. The organic particles contained in the separator of this embodiment are the organic particles provided in this embodiment.

[0251] The method for preparing the organic particles and the diaphragm in this embodiment refers to the method for preparing the organic particles and the diaphragm in Example A1, except that the methyl methacrylate in step S11 is replaced by butyl acrylate.

[0252] Comparative Example A1

[0253] This comparative example provides a separator, which is different from the separator in Example A1 in that the separator coating does not contain organic particles. The remaining features are identical.

[0254] The diaphragm preparation method of this comparative example refers to the diaphragm preparation method of Example A1. The difference from the preparation method of Example A1 is that when preparing the coating slurry, the components of the coating slurry are mixed in a ratio of organic particles: polyacrylonitrile: boehmite: water = 0%: 25%: 45%: 30%. The steps and process conditions are the same.

[0255] Comparative Example A2

[0256] This comparative example provides a separator, which is different from the separator in Example A1 in that the organic particles in the separator coating do not contain a concave structure. The other features are identical.

[0257] In addition, compared with the preparation method of the diaphragm in Example A1, the preparation method of the diaphragm in this comparative example has the following characteristics: the temperature rise rate in step S3 during drying is 20°C / min, rising to 80°C, and the heat preservation and drying time is 4 minutes.

[0258] 3. Secondary Battery Cell Example

[0259] Example B1 to Example B4 and Comparative Example B1 to Comparative Example B2;

[0260] Embodiments B1 to B4 and Comparative Examples B1 to B2 each provide a secondary battery cell, each comprising a positive electrode, a separator, and a negative electrode, and an electrolyte. The separators provided in Embodiments A1 to A4 and Comparative Examples A1 to A2 are the separators of secondary battery Embodiments B1 to B4 and Comparative Examples B1 to B2, respectively. The separator in Embodiment A1 serves as the separator in the battery cell of Secondary Battery Embodiment B1, the separator in Embodiment A2 serves as the separator in the battery cell of Secondary Battery Embodiment B2, and so on. The separator in Comparative Example A2 serves as the separator in the battery cell of Comparative Example B2.

[0261] The positive electrode was prepared as follows:

[0262] Using methyl pyrrolidone (NMP) as solvent, LiNi 0.8 Co 0.1 Mn 0.1 O2, carbon nanotubes (CNT), and binder (PVDF) were mixed in a mass ratio of 97:2:1 to prepare a positive electrode slurry with a solid content of 80%. The positive electrode slurry was evenly coated on aluminum foil, with a double-sided coating, where the surface density of each single side was 0.131g / 1540.25mm 2 After being fully dried, cold pressed and cut, the positive electrode sheet is obtained as the positive electrode.

[0263] Negative electrode: Using water as solvent, artificial graphite, conductive agent SP, dispersant (CMC), and binder (SBR) were mixed at a mass ratio of 96:1:1:2 to prepare a negative electrode slurry with a solid content of 58%. The positive electrode slurry was evenly coated on aluminum foil, with a double-sided coating, where the surface density of each single side was 0.065g / 1540.25mm 2 After being fully dried, cold pressed and cut, the negative electrode sheet is obtained as the negative electrode.

[0264] Electrolyte: Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1 at room temperature, and LiPF6 was added to the mixed solution to obtain a solution with a concentration of 1 mol / L as the electrolyte.

[0265] Secondary battery assembly: In a low-humidity constant temperature room, the positive and negative electrode sheets prepared as above are stacked and wound in the order of "positive electrode-separator-negative electrode" to form a bare cell, which is then filled with electrolyte to assemble into a lithium-ion secondary battery.

[0266] Performance testing of organic particles, separators and secondary battery cells

[0267] The organic particles, separators and secondary battery cells provided in the above embodiments and comparative examples were tested respectively.

[0268] 1. Related performance tests of organic particles:

[0269] 1.1 The organic particles of Examples A1 to A4 and Comparative Example A2 were tested for the relevant properties listed in Table 1. All test methods were in accordance with national standards (if no national standards were available, industry standard methods were used). For example, the shell thickness, the diameter of the recessed structure, and the depth of the recessed structure of the hollow particles can be measured using surface SEM, with the average of 10 tests taken. Unless otherwise specified, the volume distribution particle size Dv50 of the organic particles in this application is determined using a particle size analyzer-laser diffraction method. Specifically, the measurement can be performed using a laser diffraction scattering particle size analyzer (Mastersizer 3000 laser particle size analyzer) in accordance with the manufacturer's instructions, with reference to standard GB / T 19077-2016.

[0270] The measured results are shown in Table 1 below.

[0271] Table 1

[0272]

[0273] In conjunction with FIG9 below, it can be seen from the performance data of the organic particles in Table 1 that the organic particles in the embodiment of the present application have a specific concave structure, and the particle size and concave structure can be adjusted according to the preparation conditions.

[0274] 2. Diaphragm performance test:

[0275] 1.1 The membranes in Examples A1 to A4 and Comparative Examples A1 to A2 were tested for the relevant properties listed in Table 2. Each test method was in accordance with national standards (if no national standard was available, the industry standard method was used). For example, air permeability was tested using a membrane air permeability tester in accordance with the reference standard GB / T 36363-2018.

[0276] Diaphragm Wetting Diameter Test Method: Cut a 10cm x 10cm piece of separator, lay it flat on a glass plate, and use a dropper to add approximately 1ml of electrolyte. Use a ruler to measure the separator diameter wetted by the electrolyte within a fixed time. A larger value indicates a shorter battery filling and wetting time. The results are shown in Table 2 below.

[0277] 1.2 The separators in Examples A1 to A4 and Comparative Examples A1 and A2 were heated at room temperature (25°C) and 115°C for 15 minutes, respectively, and then subjected to scanning electron microscopy (SEM) analysis. SEM photographs of the separator in Example A1 after heating at room temperature (25°C) and 115°C for 15 minutes are shown in Figure 9 , where Figure a in Figure 9 is the SEM at room temperature (25°C), and Figure b in Figure 9 is the SEM after heating at 115°C for 15 minutes. An SEM photograph of the separator in Comparative Example A1 at room temperature (25°C) is shown in Figure 10 .

[0278] Table 2

[0279]

[0280] Combined with Figures 9 and 10, the membrane performance data in Table 2 demonstrate that the membrane of the present embodiment, by incorporating the organic particles described in the previous embodiment into its coating, imparts excellent air permeability to the membrane and improves its wettability to the electrolyte. Furthermore, the present embodiment exhibits, at least compared to Comparative Example A1, a superior ability and speed to respond to battery thermal melt. When the temperature reaches above the melting point, the organic particles melt and seal the pores of the base membrane, improving the safety of the membrane and reducing the risk of thermal runaway.

[0281] 2. Secondary battery cell performance test:

[0282] The secondary battery cells in the above-mentioned Examples B1 to B4 and Comparative Examples B1 to B2 were subjected to cycle tests at 25° C. and 1C / 1C conditions, and the test results are shown in Table 3.

[0283] Table 3

[0284] Example 0.33C rate discharge 5C high rate discharge Example B1 100% 100% Example B2 100% 98% Example B3 100% 95% Example B4 100% 100%

[0285] Comparative Example B1 100% 90% Comparative Example B2 100% 90%

[0286] When the battery is charging, the negative electrode expands, squeezing the electrolyte out of the cell. If the electrolyte does not flow back in time during discharge, the discharge capacity will be low. This phenomenon will be amplified as the discharge rate increases.

[0287] As shown in Table 3, the secondary battery cell of the embodiment of the present application contains the separator of the embodiment of the present application, which has good wettability to the electrolyte. Therefore, the electrolyte reflux ability is also strong during high-rate discharge, and the 5C discharge rate is much higher than that of ordinary separators.

[0288] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. An organic particle, characterized in that: The organic particles have a concave structure, and the concave structure is formed by a portion of the surface of the organic particles being concave inward.

2. The organic particles according to claim 1, characterized in that: The depth of the recessed structure is ≥ 0.2 μm, and may be 0.2 μm to 2.45 μm, and may be 0.4 μm to 0.65 μm; and / or The diameter of the concave structure is 0.4 μm to 4.9 μm, and can be 0.8 μm to 1.3 μm.

3. The organic particles according to claim 1 or 2, characterized in that: The organic particles are hollow particles, and the concave structure is formed by the inward concavity of a partial shell of the hollow particle.

4. The organic particles according to claim 3, characterized in that: The shell thickness of the hollow particles is 0.05 μm to 3 μm, and can be 0.15 μm to 0.2 μm.

5. The organic particles according to any one of claims 1 to 4, characterized in that: The volume distribution particle size Dv50 of the organic particles is 0.5 μm to 5 μm, and can be 1 μm to 1.5 μm; and / or The glass transition temperature of the organic particles is 90°C to 120°C, and optionally 100°C to 115°C.

6. The organic particles according to any one of claims 1 to 5, characterized in that: The organic material of the organic particles contains a polymer, and the polymer satisfies at least one of the following conditions: The weight average molecular weight of the polymer is 100,000 to 3,000,000, and can be 1,000,000 to 1,500,000; The polymer includes at least one of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, and acrylonitrile.

7. A method for preparing organic particles, characterized in that: The steps include: preparing an organic particle raw material; the interior of the organic particle raw material is filled with a volatile solvent; The volatile solvent is removed, and the surface of part of the organic particle raw material is made to be concave inward to form a concave structure, thereby obtaining organic particles.

8. The preparation method according to claim 7, characterized in that: The method for removing the volatile solvent comprises heat-treating the organic particle raw material until the volatile solvent is completely evaporated; wherein the heat treatment temperature is below the melting point of the organic particle raw material; and / or The volatile solvent includes water.

9. The preparation method according to claim 8, characterized in that: The heat treatment temperature is 40°C to 50°C, and can be 45°C to 48°C; and / or The heating rate of the heat treatment is 6°C / min to 16°C / min, and can be optionally 9°C / min to 12°C / min.

10. The preparation method according to any one of claims 7 to 9, characterized in that: The organic particle raw material is a polymer particle raw material, and the method for preparing the polymer particle raw material comprises the following steps: Carrying out a first emulsion polymerization reaction on a first polymer monomer containing a carboxyl group to obtain a first polymer particle emulsion containing a carboxyl group; Mixing a second polymer monomer with the first polymer particle emulsion to form a second polymer monomer coating layer on the outer surface of the first polymer particle, and performing a second emulsion polymerization reaction to obtain a second polymer particle emulsion; The volatile base is mixed with the second polymer particle emulsion, and the volatile base is allowed to undergo a neutralization reaction with the carboxyl group contained in the carboxyl group-containing polymer to obtain an organic particle raw material.

11. The preparation method according to claim 10, characterized in that: The mass ratio of the second polymer monomer to the first polymer particles contained in the first polymer particle emulsion is (10 to 40): (0.3 to 0.5); and / or The carboxyl-containing polymer monomer comprises at least one of acrylic acid, methacrylic acid, maleic acid and fumaric acid; and / or The second polymer monomer includes at least one of styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, and acrylonitrile.

12. A diaphragm, characterized in that: It comprises a base film and a coating layer coated on the surface of the base film, wherein the coating layer contains the organic particles according to any one of claims 1 to 6 or the organic particles prepared by the preparation method according to any one of claims 7 to 11.

13. The diaphragm according to claim 12, characterized in that Based on the total dry weight of the coating as 100%, the dry weight content of the organic particles in the coating is ≥22wt%, optionally 22wt% to 32wt%; and / or the coating further contains inorganic particle filler.

14. The diaphragm according to claim 13, characterized in that The inorganic particle filler satisfies at least one of the following conditions: Based on the total dry weight of the coating as 100%, the dry weight content of the inorganic particle filler in the coating is 16wt% to 26wt%; The volume distribution particle size D of the inorganic particle filler v 50 is 0.5μm to 5μm, and can be 1μm to 1.5μm; The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reaction.

15. The diaphragm according to any one of claims 12 to 14, characterized in that: The coating also includes a binder.

16. The diaphragm according to claim 15, characterized in that The dry weight content of the binder in the coating is 15wt% to 25wt% based on the total dry weight of the coating as 100%; and / or The thermal decomposition temperature of the binder is ≥160°C, and can be selected from 160°C to 300°C.

17. The diaphragm according to any one of claims 12 to 16, characterized in that: The thickness of the base film is 4 μm to 7 μm; and / or The coating has a thickness of 2 μm to 5 μm; and / or The surface density of the coating is 1 g / m 2 Up to 10g / m 2 , optional 2g / m 2 Up to 4g / m 2 .

18. A method for preparing a diaphragm, characterized in that: The steps include: providing a base film and a coating slurry containing organic particles; Applying the coating slurry on at least one surface of the base film, and drying the base film to form a coating to obtain a separator; The organic particles are the organic particles according to any one of claims 1 to 6 or the organic particles prepared by the preparation method according to any one of claims 7 to 11.

19. The preparation method according to claim 18, characterized in that: The coating slurry further comprises an inorganic particle filler and a binder; wherein the mass ratio of the organic polymer particles, the inorganic particle filler and the binder in the coating slurry is (22 to 32): (16 to 26): (15 to 25); and / or The coating slurry has a solid content of 30% to 40%; and / or The coating slurry has a viscosity of 100 to 1000 mPa·s at 25° C.

20. The preparation method according to claim 19, characterized in that: The binder is added in the form of a binder aqueous solution, and the binder aqueous solution has at least one of the following conditions: The viscosity of the binder aqueous solution at 25° C. is 3000 mPa·s to 10000 mPa·s; The solid content of the binder aqueous solution is 40 wt % to 50 wt %.

21. The preparation method according to any one of claims 18 to 20, characterized in that: The coating slurry is applied at a rate of 10 m / min to 100 m / min, and optionally 10 m / min to 50 m / min; and / or The drying temperature is 40°C to 50°C, and can be 45°C to 48°C; and / or The drying time is 3 minutes to 6 minutes, and can be 4 minutes to 5 minutes.

22. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator stacked between the positive electrode and the negative electrode, wherein the separator is the separator according to any one of claims 12 to 17 or the separator prepared by the preparation method according to any one of claims 18 to 21.

23. The battery according to claim 22, characterized in that The coating layer is disposed on one surface of the separator, and the coating layer faces the negative electrode.

24. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 22 or 23, and the battery is used to provide electrical energy.